2015
DOI: 10.1182/blood-2014-09-599993
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical hematopoietic transplantation from KIR ligand–mismatched donors with activating KIRs reduces nonrelapse mortality

Abstract: Key Points• Haploidentical transplantation from KIR ligand-mismatched donors with activating KIRs reduces nonrelapse mortality and improves survival.• Activating KIR genetics should be considered when selecting donors for T cell-depleted haploidentical hematopoietic transplantation.Because activating killer cell immunoglobulinlike receptors (KIRs) are heterogeneously expressed in the population, we investigated the role of donor activating KIRs in haploidentical hematopoietic transplants for acute leukemia. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 73 publications
2
85
0
Order By: Relevance
“…Also donor-derived, mature NK cells, lost in the procedure of positive selection of CD34 1 cells and spared in our ab T-cell-depleted graft, exhibit a graft-versus-leukemia (GVL) effect 6,10,[14][15][16]41,42 and participate in the control of opportunistic infections, including HCMV. [43][44][45] In previous studies, we documented that in haplo-HSCT recipients given positively selected CD34 1 cells, ;8 weeks after transplantation are needed to detect mature KIR 1 NK cells, and this gap in reconstitution may favor early leukemia relapse in the case of high residual tumor burden and/or rapidly proliferating blasts. 14,16 Through the approach of selective ab T-and B-cell depletion, the recipient immediately benefits from high numbers of donor mature NK cells that can fully display their activity, because the recipient is not exposed to the effect of pharmacological prophylaxis of GVHD, which can impair differentiation/expansion of this lymphocyte subset.…”
Section: Discussionmentioning
confidence: 99%
“…Also donor-derived, mature NK cells, lost in the procedure of positive selection of CD34 1 cells and spared in our ab T-cell-depleted graft, exhibit a graft-versus-leukemia (GVL) effect 6,10,[14][15][16]41,42 and participate in the control of opportunistic infections, including HCMV. [43][44][45] In previous studies, we documented that in haplo-HSCT recipients given positively selected CD34 1 cells, ;8 weeks after transplantation are needed to detect mature KIR 1 NK cells, and this gap in reconstitution may favor early leukemia relapse in the case of high residual tumor burden and/or rapidly proliferating blasts. 14,16 Through the approach of selective ab T-and B-cell depletion, the recipient immediately benefits from high numbers of donor mature NK cells that can fully display their activity, because the recipient is not exposed to the effect of pharmacological prophylaxis of GVHD, which can impair differentiation/expansion of this lymphocyte subset.…”
Section: Discussionmentioning
confidence: 99%
“…by identifying the presence of the KIR2DS1 locus 58 or by identifying KIR B haplotype-positive donors. 59,60 An even more sophisticated approach would take into account the KIR2DL1 allelic polymorphism affecting the strength of the inhibitory receptor.…”
Section: Haploidentical Donorsmentioning
confidence: 99%
“…In addition, KIR3DS1 was also found to associate with lower rate of relapse and infection. Mancusi A et al reported KIR3DS1 was associated with reduced infection mortality [115]. Further studies are still needed to identify ligands for activating KIR so as to confirm the effect of each activating KIR gene on allo-HSCT outcome.…”
Section: Donor Killer Immunoglobulin-like Receptors Affect Beneficialmentioning
confidence: 99%